Faktor-faktor yang Mempengaruhi Keputusan Masyarakat Muslim Dusun Rantau Rasau Menggunakan Jasa Bank Konvensional dibandingkan Bank Syariah - Manullang, Zuly Nanda; Rafidah, Rafidah (ALSYS, 2025)
The rapid development of the global economy, including in Indonesia, has encouraged the public to be more selective in choosing financial institutions that meet their individual or organizational fund management needs. In this context, society is faced with the choice between conventional banks and Islamic banks. This study aims to identify the factors influencing the decision of the Muslim community in Dusun Rantau Rasau to use conventional banking services and to explore the reasons behind their non-use of Islamic banks. A descriptive qualitative approach was employed through field research. Primary data were obtained through direct interviews and observation, while secondary data were sourced from books, journals, and historical records of Dusun Rantau Rasau. The results reveal that five main factors influence the preference for conventional banks: knowledge, social influence, promotion, culture, and ease of access. Meanwhile, the predominant reasons for not choosing Islamic banks include limited knowledge and minimal promotional exposure. Additionally, informants emphasized that loyalty and a broader understanding of conventional banking services significantly affect their preferences. In conclusion, knowledge stands out as a crucial factor in financial institution selection, followed by loyalty and exposure to promotional strategies.